2015
DOI: 10.1074/jbc.m115.653543
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Arginine Methylation of Tumor Necrosis Factor (TNF) Receptor-associated Factor 6 Regulates Toll-like Receptor Signaling

Abstract: Background: Innate immune signaling requires multiple mechanisms to suppress signaling in the absence of stimulation. Results: TNF receptor associated factor 6 (TRAF6) activity is regulated by reversible arginine methylation. Conclusion: Arginine methylation of TRAF6 inhibits signaling in the absence of Toll-like receptor ligands. Significance: Reversible TRAF6 methylation is a novel mechanism that controls innate immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 29 publications
(34 reference statements)
1
64
0
Order By: Relevance
“…One of the mechanisms by which ethanol exacerbates HCV pathogenesis is via an impaired methylation-dependent interferon signaling in hepatocytes that prevents protective antiviral interferon-stimulated gene activation (17). The role of methylation-dependent dysregulation of innate immunity by ethanol in HCV-infected liver cells has also been shown by others (54). The deficiency in innate immunity suggests that the level of HCV RNA should at least be doubled in alcohol-exposed liver cells.…”
Section: Discussionmentioning
confidence: 89%
“…One of the mechanisms by which ethanol exacerbates HCV pathogenesis is via an impaired methylation-dependent interferon signaling in hepatocytes that prevents protective antiviral interferon-stimulated gene activation (17). The role of methylation-dependent dysregulation of innate immunity by ethanol in HCV-infected liver cells has also been shown by others (54). The deficiency in innate immunity suggests that the level of HCV RNA should at least be doubled in alcohol-exposed liver cells.…”
Section: Discussionmentioning
confidence: 89%
“…Given that type I PRMTs are known to control NF-κB target genes (18)(19)(20)(21)(22), we investigated whether Rel proteins are modified by asymmetric arginine dimethylation. We tested PRMT1, PRMT4, and PRMT6, all of which are present in the nucleus and modify histones, for their ability to methylate the RelA subunit of NF-κB.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that PRMT1 and PRMT5 methylate SPT5 and repress its promoter association and interaction with RNApol II, resulting in a lower rate of transcriptional elongation. It also has been reported that under basal conditions, the ubiquitin ligase activity of TNF receptorassociated factor 6 is impaired by PRMT1-mediated methylation, resulting in inhibition of NF-κB (22). It is likely that PRMT1-mediated regulation of NF-κB target genes requires methylation of other proteins involved in transcription or upstream of NF-κB.…”
Section: (7)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although suppression of STAT1 methylation was mainly attributed to PRMT1 dysfunction, we cannot exclude that HCV-induced demethylation of STAT1 also regulates IFNα signaling. In fact, it has been shown recently that the methylation of another innate immunity regulator, TNF receptor-associated factor 6 (TRAF6), is partially controlled by demethylase Jumonji domain-containing protein 6 (JMJD6) [8]. The JMJD6 is a non-heme Fe(II) 2-oxoglutarate (2OG)-dependent oxygenase with bifunctional enzymatic activities, arginine demethylase and lysyl hydroxylase [9,10].…”
mentioning
confidence: 99%